ANALISIS PEMBENTUKAN KATA BAHASA GAUL BAHASA INGGRIS YANG DIGUNAKAN DALAM LIRIK LAGU POLO G - Lakeisha Annisa Choiroh; Meita Lukitawati Sujatna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
There were two different speech patterns that may be classified as formal and informal type. Informal speech pattern is also well-known as slang. The informal one was popularly referred to as slang. Slang was an informal language that was formed by a particular group of people and utilized by teens in the contemporary period. Slang was used not just in everyday speech but also in literary works such as songs. A song was a literary work that could both depict reality and convey a person’s emotions. This research uses a descriptive qualitative technique to analyse the slang terms that may be found in seven of Polo G’s song’s lyrics. The word class and the slang’s word formation are the main topics of this research. There are 8 data of information have been gathered from the lyrics. The study indicates that slang terminology like “blending”, “clipping”, and “acronym” are used in the lyrics. According to the research the slang terms utilized in the lyrics such as blending, clipping, acronym. And coinage. Mostly, the word formation in the Polo G’s song lyrics is produced by the process of clipping and acronym. Keywords: Slang, Song lyrics, Types of Word Formation, Word Formation